Ten new species and thirteen new country records for the Neotrichia canixa species group (Trichoptera: Hydroptilidae) in Costa Rica - Harris, Steven C.; Armitage, Brian J.; Holzenthal, Ralph W. (Zootaxa, 2026)
Formerly, only one species of Neotrichia, N. esmalda (Mosely), was recorded from Costa Rica. In this publication, we add 10 new species (N. alajuela sp. nov., N. cerberusi sp. nov., N. chaconorum sp. nov., N. doshocica sp. nov., N. gancho sp. nov., N. monika sp. nov., N. munozi sp. nov., N. paragancho sp. nov., N. pejensis sp. nov., N. trescuerna sp. nov.) and 13 new country records, all belonging to the Neotrichia canixa species group, to Costa Rica’s fauna. We also discuss and acknowledge transfer of all the former Neotropical members of the Neotrichia esmalda species group to the Neotrichia canixa species group. There are now 24 species of Neotrichia known from Costa Rica, all of which are in the same species group.